(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Blockchain technology, which would be the underlying technology, has recently become very popular with the increase in cryptocurrencies and is being used in IoT and other fields. There have been shortfalls, however, which impede its implementation, including the volume of space. Transactions will be produced at a significant level due to the huge amount of Connected systems that often work in many networks as data processors. In IoT, the storage issue will become more intense. Current storing data platforms have a wide range of features to respond to an extensive variety spectrum of uses. Nevertheless, new groups of systems have arisen, e.g., blockchain with data version control, fork semantics, tamper-evidence or some variation thereof, and distributed analysis. They’re showing new challenges for storage solutions to effectively serve such energy storage Systems by integrating the criteria mentioned in the processing. This paper discusses the potential security and privacy concerns of IoT applications and also it is shown that in first step the storage is enhanced by 50% and further in the next step, it is improved and it takes only 256 bytes irrespective of the input data size.